Analytical and experimental investigation on heat transfer and flow parameters of Multichannel louvered fin cross flow heat exchanger using iterative LMTD and ∊-NTU method. (2022) - Vinoth Kumar, D.; Vijayaraghavan, S.; Thakur, Praveen
Abstract: Automotive Heat exchangers plays vital role by ensuring human comfort in cabin by maintaining optimum temperature and maintains operating temperature of Internal Combustion(IC) engine within permissible limits. In this work, iteration based mathematical model to solve for analytical thermo-hydraulic performance estimation of a typical heat exchanger is adopted with Log Mean Temperature Difference (LMTD) method by incorporating the variation in properties of fluids during each iteration, since the overall thermal resistance ratio between targeted & calculated Heat Rejection Rate (HRR) has to be converged to unity to solve for the actual thermal performance of the heat exchanger. This condition ensures convergence and there is no deviation between the two adjacent iterations in terms of HRR value. Additionally, the above condition ensures that deviation between analytical value calculated by Effectiveness-NTU (∊-NTU) method and experimental data will be reduced significantly due to the proposed iterative LMTD approach adopted in this work. Along with iterative LMTD methodology, ∊-NTU method is adopted for last iteration to cross-verify the obtained value of the HRR for same operating conditions. In order to evaluate heat transfer coefficients for air and coolant side, standard correlations are used from well-established and validated literature data. For coolant side pressure drop calculations, network solution methodology is adopted where fluid flow behavior in each segment of heat exchanger is studied in detail and analytical relationships are used to predict net pressure drop in entire heat exchanger. In our mathematical model, louvered fin effects on heat transfer is taken into account by adopting colburn approach and the geometrical effects of internal fins on flow channels is also included. Experimental validations tests are carried out to compare with the analytical results of HRR, Coolant Side Pressure Drop (CSPD) and Air Side Pressure Drop (ASPD) across heat exchanger. A good agreement is found between experimental and analytical results which validates the accuracy of present mathematical model and methodology, the maximum deviation for HRC is 4% on higher side, for CSPD and ASPD it is 15.4%, 8.7% on higher side respectively.